An Existing Profit Evaluation Model and Its an Alternative Profit Evaluation Model based on Shariah-Compliant - Gazali, Nadhirah; Abdul Halim, Nurfadhlina; Liza Ghazali, Puspa; Mamat, Mustafa; Muhamad Amir W. Ahmad, Wan (International Journal of Engineering and Technology, 2018)
In Malaysia, financing in Islamic finance is divided into two concepts that are equity financing and loan financing. This both concepts have been modified to fulfill consumerâ€™s need and the model should abide the law of Shariah. The model refers to evaluation of profit formula known as Constant Rate of Return (CRR) is widely used in Islamic financing. Besides that, the profit generate is based on the profit rate. The determination of profit rate is based on reference rate which is known as base rate (BR) or base financing rate (BFR) as a proxy. However, there are lacks of Shariah perspective in the formulaâ€™s framework and also the formulation used nowadays where there is no significant difference with the conventional financing. Therefore, an alternative profit known as base profit rate (BPR) was build based on Islamic jurists and a new profit rate has been introduced for Islamic financing. Hence, the intention of this paper is to investigate between CRR model and BPR model based on Shariah perspective.Â Â